Decoding M&As Dynamics in the Indo-Pacific : Insights from QUAD Countries - Jain, Divya; Singh, Archana (Indian Journal of Finance, 2026)
Purpose : This study examined the impact of key macroeconomic factors (liquidity, gross domestic product (GDP), real effective exchange rate (REER), consumer price inflation (CPI), and real interest rate) on mergers and acquisitions (M&As) volumes within the QUAD countries (Australia, India, Japan, and the United States), evaluating domestic, inbound, and outbound M&As segments. Methodology : The research employed a negative binomial fixed-effects panel regression model to analyze M&As activity for each QUAD country individually and as a collective bloc. Findings : The study revealed that foreign direct investment (FDI) consistently influenced all types of M&As activities across the QUAD bloc. Liquidity and REER exhibited varying effects depending on the M&As segment, while GDP, inflation, and interest rates showed moderate and segment-specific impacts, underlining the complex interaction between macroeconomic conditions and cross-border investments. Practical Implications : This research contributed to the limited literature on M&As by focusing on the strategic role of macroeconomic stability in the QUAD countries. The findings provided valuable guidance for policymakers and firms involved in strategic cross-border transactions within the Indo-Pacific region. Originality : Unlike prior research focusing on BRICS economies, bilateral FDI, or target-country factors, this study provided the first systematic evidence on how macroeconomic factors shaped M&A activity in QUAD countries.